An analysis of effects of retailer-supplier relationships on company competitiveness: case of TM Pick ‘n Pay Gweru - Mutero, Valerie Vimbiso (Midlands State University, 2018)
This research was carried out to analyze the effect of retailer-supplier relationships on company competitiveness; a case study of TM Pick ‘n Pay Gweru branch supermarket. The study had three objectives, to determine the role of collaborative partnerships on enhancing company competitiveness, to establish strategies to maintain long-term successful retailer-supplier relationships and to determine challenges facing retailer that leads to business to business relationship failures. The research design involved a survey of thirty-one respondents purposively sampled from the retailer management, employees and supplier agents. Data was collected using face to face interviews and questionnaires that were administered through “drop and pick” method. Percentages and frequencies were used to analyze the objectives and the findings are presented in tables, graphs and charts. The study findings denotes that utilization of resources, enhanced procurement performance, forecast accuracy and mutual benefits are the outcome of collaborations that are achieved through trust, commitment, information sharing and mutual goal planning; the absence of these are the challenges the buyer and supplier face. The researcher has recommended retail companies and other organizations to embrace buyer-supplier relationships so as to reap the benefits; ensure effective communication between buyer and supplier to counter challenges associated with relationship management.